Broccoli Leaves Attenuate Influenza A Virus Infection by Interfering With Hemagglutinin and Inhibiting Viral Attachment - Cho, Won-Kyung; Yim, Nam-Hui; Lee, Myong-Min; Han, Chang-Hoon; Ma, Jin Yeul (Frontiers in Pharmacology, 2022)
Broccoli (Brassica oleracea L. var. Italica) leaves are a byproduct of broccoli and could be used as a food source. The study aimed to evaluate the effect of broccoli leaves on influenza A virus (IAV) infection. We investigated the effect of ethanol extract of Broccoli leaves (EBL) on IAV infection using green fluorescent protein (GFP)-tagged Influenza A/PR/8/34 virus (PR8-GFP IAV). When EBL and PR8-GFP IAV were cotreated to the RAW 264.7 cells, the fluorescent microscopy and fluorescence-activated cell sorting (FACS) analysis showed that EBL significantly reduced the levels of GFP expression by influenza viral infection, dose-dependently. Immunofluorescence (IF) analysis confirmed that EBL decreased the expression of IAV HA protein. EBL exhibited a strong inhibitory effect of IAV binding on the cells and moderate virucidal impact. Consistently, EBL potently suppressed the hemagglutination by IAV infection. These results indicate EBL prevents IAV attachment via the inhibition of HA upon viral infection. Finally, EBL as an HA inhibitor of IAV could be used as the natural antiviral source to protect against influenza viral infection.